Restored CD8+PD-1+ T Cells Facilitate the Response to Anti-PD-1 for Patients With Pancreatic Ductal Adenocarcinoma - Zhu, Qian; Qiao, Guoliang; Huang, Lefu; Xu, Chang; Guo, Deliang; Wang, Shuo; Zhao, Jing; Song, Yuguang; Liu, Bing; Chen, Zheng; Yang, Zhiyong; Yuan, Yufeng (Frontiers in Oncology, 2022)
Background & Aims: We aimed at to investigate that restoring the amount of CD8+PD1+ T cells through adoptive T cell therapy (ACT) could improve the prognosis and facilitate the therapeutic response to anti-PD-1 in patients with advanced pancreatic cancer (APC). Methods: 177 adult patients who underwent tumor resection as initial treatment for PDAC during February 2013 to July 2019. at Zhongnan Hospital of Wuhan University were enrolled in this study. Another cohort of 32 patients with APC were prospectively enrolled from Capital Medical University Cancer Center, Beijing Shijitan Hospital from June 1, 2013, to May 30, 2019. All patients with APC underwent ACT and 15 of 32 (46.8%) patients received ACT combined with anti-PD-1 (Pembrolizumab). Results: Of the 177 patients received tumor resection, 67 tumor samples showed overexpression of PD-L1 We found that high PD-L1 expression in tumor tissues was significantly associated with short overall survival. Also, we tested the percentage of peripheral CD8+PD-1+ T cells and found it was significantly correlated with the PD-L1 expression and the prognosis of patients with PDAC. We further tracked the peripheral blood T lymphocyte subtypes for 30 months and found that CD8+PD-1+ cells were decreased and we hypothesized that the CD8+PD-1+ cells were exhausted. After that, we performed ACT for patients with APC and we found that the ratios of post treatment of ACT/pre-ACT CD8+PD-1+ T cells were significantly related with the prognosis of patients with APC. Moreover, patients with combined treatment of ACT with anti-PD-1 had significantly favorable both OS and PFS. Furthermore, T-cell receptor (TCR) repertoire were tested and TCR diversity of cultured T cells were calculated and we found the treatment of ACT impacted on the TCR repertoire especially in patients with significantly CD8+PD-1+ T cells enhanced. Conclusions: this study showed that the CD8+PD-1+ T cell subgroup was related with expression of PD-L1 and the prognosis of patients with PDAC who received surgical resection. The CD8+PD-1+ T cells were gradually exhausted and restoring it by treatment of ACT was associated with a significantly favorable prognosis and facilitate the response to Anti-PD-1.